Blood-brain barrier and brain edema - Platten, Michael; Wick, Wolfgang (Neuro-oncology ; 1, 2012)
The function of the blood-brain barrier (BBB) continues to be a diagnostic and therapeutic challenge for physicians treating patients with central nervous system (CNS) malignancies. Despite its physiological importance, only a few clinical studies have specifically addressed the role of the BBB in the biology of brain tumors. Peritumoral vasogenic edema as a result of BBB dysfunction within the tumor affects neurological function and quality of life, and may even cause life-threatening raised intracranial pressure. Thus, treatment of brain edema continues to be a mainstay in the palliative care of patients with malignant brain tumors. Conversely, the limited efficacy of chemotherapeutic agents used to treat patients with malignant brain tumors is, in part, due to their inability to penetrate the BBB in noncontrast-enhanced areas of the tumor and to achieve meaningful tumoricidal concentrations within the tumor tissue. In this chapter we discuss functional and dysfunctional aspects of the BBB in CNS malignancies and the consequences thereof for the treatment of patients with brain tumors.